Pemanfaatan Limbah Kulit Kakao Sebagai Bahan Pembuat Pori Pada Ecopavings Block - Erlangga, Erlangga; Rahmawati, Winda; Amin, Muhammad; Suharyatun, Siti (Jurnal Agricultural Biosystem Engineering, 2023)
During 2018-2019 there were floods in the Bandar Lampung area. In general, the flood that occurs is only inundation with a maximum height of 2 meters. Therefore, every residential area or roadside must have water catchment areas such as a stretch of land in the form of planting or sidewalks that have pores such as paving blocks that can absorb rainwater into the ground. Making paving blocks in this study used cocoa shell waste because it was indicated that it could be processed into charcoal which contains a lot of carbon which can absorb water, with this composition absorbing water between eco-pavings blocks. The purpose of this research is to utilize cocoa shell waste to manufacture eco-paving blocks and to analyze the physical characteristics of cocoa shell eco-paving blocks. The effect of cocoa shell waste on Eco-Paving Blocks in this study is that the more cocoa shell waste fiber is used, the more porous cavities in the eco-paving block will be, and vice versa. The paving block of cocoa shell waste produced in this study has an average density test value of 1670.751 kg/m3 to 1929.642 kg/m3. The water absorption test obtained an average value of 11.18% - 19.82%. For the infiltration test, the largest value was obtained, namely in treatment 1, which was 0.355 mm/s. The visible test is obtained with the shape of the appropriate paving texture obtained on the P2 factor because the resulting texture is good and there are no gaps or defects when the paving has been printed. Meanwhile, in the compressive strength test, the average value decreased significantly from the P1 variation to the P4 variation. The highest value was in treatment P1 with a value of 0.0154 MPA, while the lowest value occurred in treatment P4 with a value of 0.0030 MPA. However, in this study there were several parameters that did not meet the criteria for quality standard paving D. Keywords: Eco-Paving Block, Cocoa Shell Waste